2015
DOI: 10.1080/08870446.2015.1061129
|View full text |Cite
|
Sign up to set email alerts
|

Young adult e-cigarette users’ reasons for liking and not liking e-cigarettes: A qualitative study

Abstract: Objective To gain an in-depth understanding of what young adult electronic- or e-cigarette users like or dislike about e-cigarettes. We aimed to determine the reasons that may encourage young adults to use e-cigarettes or discourage them from using e-cigarettes. Design Twelve focus group discussions were conducted with 62 current daily e-cigarette users (63% men) of mean age = 25.1 years (Standard Deviation = 5.5). Data were analyzed following principles of inductive content analysis. Results Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
134
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 39 publications
15
134
0
3
Order By: Relevance
“…This can be a possible explanation for the association between reasons for use of e-cigarettes and the continued use of them. On the other hand, e-cigarettes can be used as a recreational device in terms of the purpose of ecigarette uses, even in non-smoking adolescents [29]. Our findings show e-cigarettes were used as a smoking cessation aid among adolescent smokers and for recreational purposes even among nonsmokers, although there is lack of evidence for their safety and efficacy in adolescents [26,27].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This can be a possible explanation for the association between reasons for use of e-cigarettes and the continued use of them. On the other hand, e-cigarettes can be used as a recreational device in terms of the purpose of ecigarette uses, even in non-smoking adolescents [29]. Our findings show e-cigarettes were used as a smoking cessation aid among adolescent smokers and for recreational purposes even among nonsmokers, although there is lack of evidence for their safety and efficacy in adolescents [26,27].…”
Section: Discussionmentioning
confidence: 60%
“…For infrequent e-cigarette users, curiosity, better taste, and good flavor comprised half of the reasons for e-cigarette use. This group initiates e-cigarette use for recreational purposes [29], and this can increase the probability of their becoming conventional cigarette smokers or other substance users [9].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is converging that e-cigarettes provide an opportunity for smokers to redefine themselves from “smokers” to “vapers” (Barbeau et al, 2013). Given the loss of identity and social engagement reported by individuals who quit smoking, the social characteristics may be a particularly appealing aspect of transitioning from smoking to vaping (Pokhrel et al, 2015b). Additionally, our study participants felt they were able to escape the stigma of being a “smoker” by referring to themselves as a “vaper.” A few participants referred to the e-cigarette as a “vaporizer” to avoid using the word “cigarette,” thereby further distinguishing use from traditional cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Negative perceptions of e-cigarettes have included feelings of uncertainty surrounding the safety of e-cigarettes and conflicting views related to the potential for continued nicotine addiction (Pokhrel et al, 2015b; Rooke, Cunnigham-Burley, & Amose, 2015). A recent examination of open-ended responses on a survey conducted with e-cigarette users (Baweja et al, 2015) found that the most common negative effects of e-cigarettes mentioned were dry mouth, chapped lips, and bad breath.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous qualitative studies have focused on perceptions and reasons for user among e-cigarette users, but have not examined differences in perceptions among e-cigarette users versus nonusers. 17,5153 Therefore, the current study provides much-needed insight into the beliefs of nonusers. By examining differences in perceptions by e-cigarette use category, the current study identified similarities and differences in themes between the 2 groups.…”
Section: Commentmentioning
confidence: 99%